Preventative Care in First Responder Mental Health: Focusing on Access and Utilization via Stepped Telehealth Care - Wright, Hannah M.; Fuessel-Hermann, Dianna; Pazdera, Myah; Lee, Somi; Ridge, Brook; Kim, Joseph U.; Konopacki, Kelly; Hilton, Layne; Greensides, Michael; Langenecker, Scott A.; Smith, Andrew J. (Frontiers in Health Services, 2022)
First responders are at high risk for disorders that arise from repeat exposure to stress and trauma (Post Traumatic Stress Disorder, depression, and problematic alcohol use). Although mental health treatments are available, first responders often do not access them, anchored by barriers that include: lack of knowledge, stigma, negative experience with mental health providers, and time-based burdens. In this study, we designed an intervention to address these barriers, extending a Planned-Action framework. Step 1 involved self-report screening for four mental health risks (PTSD, depression, anxiety, and alcohol use risk), delivered to all personnel electronically, who were free to either consent and participate or opt-out. The detection of risk(s) in Step 1 led to scheduling a Step 2 telehealth appointment with a trained clinician. We report descriptive statistics for participation/attrition/utilization in Steps 1 and 2, rates of risk on four mental health variables, and rate of adherence to follow-up treatment recommendations. Step 1: In total, 53.3% of personnel [229 of 429 full-time employees (221 males; eight females; 95% White; 48% paramedic or Emergency Medical Technician; 25% captain; 19% engineer; 7% other)] initially opted-in by consenting and completing the brief remote screening survey. Among those who opted-in and completed (n = 229), 43% screened positive for one or more of the following mental health risks: PTSD (7.9%); depression (9.6%); anxiety (13.5%); alcohol use (36.7%). Step 2: A maximum of three attempts were made to schedule “at risk” individuals into Step 2 (n = 99). Among the 99 who demonstrated a need for mental health treatment (by screening positive for one or more risk), 56 (56.6%) engaged in the telehealth appointment. Of the 56 who participated in Step 2 clinical appointments, 38 were recommended for further intervention (16.6% of full-time personnel who participated). Among the 38 firefighters who were recommended to seek further mental health services, 29 were adherent/followed through (76.3% of those who received recommendations for further services). Taken together, evidence-based, culturally conscious, stepped care models delivered via the virtual/telehealth medium can promote access, utilization, and cost-effective mental health services for first responders. Implications are for informing larger, more rigorous dissemination and implementation efforts.